Cognitive Flexibility and Resilience in Adolescents: Exploring Gender Differences and Cultural Implications - Artawijaya, Lintang Mahardhika; Supratiwi, Mahardika (Utan Kayu Publishing, 2024)
This study explores the role of cognitive flexibility in enhancing resilience among Indonesian adolescents, using a cross-sectional research design. A total of 152 high school students from grades 10 and 11 participated, with data collected through the Cognitive Flexibility Scale (CFS) and the Brief Resilience Scale (BRS). The findings revealed a significant positive relationship between cognitive flexibility and resilience, indicating that cognitive flexibility is a crucial predictor of resilience. The study also identified significant gender differences in resilience, with male adolescents exhibiting higher resilience levels than females. These results align with existing research, emphasizing the importance of cognitive flexibility in psychological well-being and stress management. Furthermore, the study contributes to the broader literature by demonstrating that the relationship between cognitive flexibility and resilience is robust across different cultural contexts, including Indonesia. The practical implications of these findings are substantial, suggesting that educational programs should integrate cognitive flexibility into school curricula through targeted teacher training and specialized learning modules. Additionally, the development of gender-specific interventions is recommended to address the distinct needs of male and female adolescents. Future research should further investigate the mechanisms underlying the relationship between cognitive flexibility and resilience, particularly considering potential moderating factors such as family environment and school context. Longitudinal studies would be beneficial to track the development of these traits over time, providing deeper insights into their dynamic interaction. Understanding cultural influences on these constructs is also crucial for designing culturally appropriate and effective interventions.